Macroeconomic effects of global shocks in the GCC: evidence from Saudi Arabia. Issue 2 (3rd July 2022) - Mohaddes, Kamiar; Raissi, Mehdi; Sarangi, Niranjan
ABSTRACT : We develop a quarterly macro-econometric model for the Saudi economy over the period 1981Q2-2018Q2 and integrate it within a compact model of the world economy (including the global oil market). This framework enables us to disentangle the size and speed of the transmission of growth shocks originating from the United States, China, and the world economy to Saudi Arabia, as well as study the implications of stress in global financial markets, low oil prices, and domestic fiscal adjustment on the Saudi economy. Results show that Saudi Arabia's economy is becoming more sensitive to developments in China than to shocks in the United States – in line with the direction of evolving trade patterns and China's growing role in the global oil market. A global growth slowdown (e.g. from trade tensions or geopolitical developments) could have significant implications for Saudi Arabia (with a growth elasticity of about 2½ after one year) and the oil market (reducing prices by about 5% for 0.5 percentage point reduction in global growth). We also illustrate that a 10% lower oil prices and stress in global financial markets could both have a negative effect on the Saudi economy, but given the prevailing social contract in Saudi Arabia, their impact is countered by fiscal easing. Finally, we observe that a domestic fiscal adjustment in Saudi Arabia does not show a negative impact on economic growth in the data. The impact on growth would depend upon the quality of fiscal adjustment and whether it is complemented with structural reforms.